Implikatur Ekspresi Tindak Tutur Verdiktif Srimpi Anglir Mendhung - Maryono, Maryono (PANGGUNG, 2019)
ABSTRACTUnderstanding of art will be complete if it can express a particular value. One source of values in art is the pleasure of its objectivity, which encompasses intrinsic and extrinsic values with aesthetical visualization. The values of implicature in the Srimpi Anglir Mendhung can be found by referring to the expression of verdictive speech acts in its verbal and nonverbal components. In order to study the implicature values contained in Srimpi Anglir Mendhung, the researcher uses a qualitative research methodology based on the theory of pragmatics and theory of performing arts. The strategies used for collecting data are a library study, a study of visual recordings, a study of audio recordings, and interviews. The technique of analysis is interactive and involves the triangulation of data, methodology, and theory. The results of the discussion show that the implicature in the expression of verdictive speech acts in Srimpi Anglir Mendhung is a form of adulation and homage to the noble king, Sultan Agung Hanyakra Kusuma from the Mataram Kingdom. The values of heroism and virtue contained in Srimpi Anglir Mendhung are a reflection of the values of life, which should be emulated and appreciated by the audience and general public.Keywords: implicature, expression of verdictive speech acts, and Srimpi Anglir Mendhung dance. ABSTRAKPemahaman tentang seni terjadi secara lengkap apabila mampu untuk mengungkapkan suatu nilai. Satu sumber nilai seni adalah kenikmatan yang diberikan oleh objektifitas terhadap nilai-nilai instrinsik dan ekstrinsik dengan visualisasi estetis. Merujuk pada ekspresi tindak tutur verdiktif pada komponen verbal dan nonverbal, Tari Srimpi Anglir Mendhung dapat ditarik implikatur nilainya. Untuk mengkaji implikatur nilai yang terkandung dalam Tari Srimpi Anglir Mendhung, peneliti menggunakan metodologi penelitian kualitatif dengan berlandaskan teori pragmatik dan teori seni pertunjukan. Strategi pengumpulan data berupa studi pustaka, studi rekaman visual, studi rekaman audio, dan wawancara. Teknik analisisnya bersifat interaktif dengan mentrianggulasikan data, metodologis, dan teori. Hasil pembahasan ditemukan bahwa implikatur ekspresi tindak tutur verdiktif Srimpi Anglir Mendhung merupakan bentuk sanjungan dan penghormatan terhadap raja yang dimuliakan yaitu Sultan Agung Hanyakra Kusuma dari Kerajaan Mataram. Nilai-nilai keprajuritan dan kebajikan yang terkandung dalam Srimpi Anglir Mendhung merupakan cerminan nilai-nilai kehidupan, layak diteladani dan diapresiasi oleh audiens maupun masyarakat luas.Kata kunci: ekspresi, implikatur, Tari Srimpi Anglir Mendhung, tindak tutur verdiktif